2017
DOI: 10.1016/j.ribaf.2016.02.002
|View full text |Cite
|
Sign up to set email alerts
|

Determinants of the capital adequacy ratio of foreign banks’ subsidiaries: The role of interbank market and regulation

Abstract: This paper examines the factors influencing the capital adequacy ratio (CAR) of foreign banks. We test whether the CAR of subsidiaries and branches in developed and developing countries depends on the same factors. We use data from 310 subsidiaries and 265 branches to test the impact of the parent banks' fundamentals on subsidiaries' and branches' capital ratios. We also study how the economic condition and regulatory environment in a bank's home country determine foreign banks' CAR. Our results provide strong… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
42
0
11

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 56 publications
(61 citation statements)
references
References 39 publications
8
42
0
11
Order By: Relevance
“…This study is in line with research conducted Thoa & Anh (2017) found that the loan asset ratio has a significant negative effect on capital adequacy ratio. This research is supported by research conducted by Mili et al (2017) who argued that the loan asset ratio has a negative effect on capital adequacy ratio. An increase in the loan tends to decrease the CAR, which explains that capital regulation may decrease after the extension of the crediting period.…”
Section: |supporting
confidence: 53%
See 1 more Smart Citation
“…This study is in line with research conducted Thoa & Anh (2017) found that the loan asset ratio has a significant negative effect on capital adequacy ratio. This research is supported by research conducted by Mili et al (2017) who argued that the loan asset ratio has a negative effect on capital adequacy ratio. An increase in the loan tends to decrease the CAR, which explains that capital regulation may decrease after the extension of the crediting period.…”
Section: |supporting
confidence: 53%
“…Buyuksalvarci & Adioglu (2011) analyzed the factors affecting the capital adequacy ratio of LOA results showed that credit (LOA) had a negative effect on CAR. Mili et al (2017) argue that an increase in the loan tends to decrease CAR. This explains the regulation of capital may decrease after the extension of the crediting period.…”
Section: Determinants Of Capital Adequacy Ratio On Banking Industry: mentioning
confidence: 99%
“…Evidence showed that bank size was inversely related to CAR whereas profitability, liquidity and riskiness, as measured by the quality of the asset portfolio, were shown to be statistically insignificant in explaining CAR. A study by Mili et al (2014), using a dataset of multinational banks, examined empirically the factors that affect CAR. They used among other factors, macroeconomic factors as well as variables related to the bank's subsidiaries.…”
Section: Literature Review and Hypotheses Developmentmentioning
confidence: 99%
“…Results showed that firm size was the only factor that affects capital adequacy, whereas profitability, liquidity and asset quality were shown to be insignificant in explaining capital adequacy. Mili, Sahut, and Trimeche (2014), using a dataset of multinational banks, showed that bank's size is inversely related to Capital Adequacy Ratios (CAR) whereas some riskiness and profitability measures were shown to affect positively CAR. They also showed that some other profitability ratios, such as return on assets (ROA) do no affect CAR.…”
Section: Introductionmentioning
confidence: 99%
“…One of the factors influencing the determination of the amount of bank capital is the amount of the costs necessary to restore the capital. Banks, which are seeking to avoid the costs associated with the reconstruction of the capital in a very short period of time, tend to hold more capital than it is required by the supervisory authorities (Peura, Keppo, 2006). This capital in the scientific literature is named a buffer capital.…”
Section: Review Of Theory and Literaturementioning
confidence: 99%